Hubungan antara Paritas Dengan Posisi Menyusui Yang Benar Pada Ibu Nifas di RS Muhammadiyah Dan RS Muslimat Kabupaten Ponorogo - muniati murniati; Prasidharasmi Striratna Winayaiswari (Jurnal Delima Harapan, 2018)
Results of preliminary studies that have been conducted in the postpartum HospitalMuhammadiyah Ponorogo and Ponorogo in 10 respondents with observations on August10, 2016 obtained 7 respondents (70%) with a breastfeeding is True Position, 3respondents (30%) with a nursing position skilled. From 7 to mothers with less skillednursing position in an entirely get primiparas. Thus allowing the lack of skilled due to alack of experience on postpartum mother for the first time to breastfeed her baby. Thepurpose of this study to determine the relationship Parity with Breastfeeding PositionsRight On Mother Postpartum hospital and the hospital's Muhammadiyah PonorogoPonorogo.The design study is an analytic correlational with cross sectional approach. Theresearch location in Hospital’s Women Muhammadiyah Ponorogo Ponorogo, conductedin September 2016. The population is all breastfeeding mothers in Hospital’sMuhammadiyah Ponorogo Ponorogo, the month August 2016 the number of 30, with asample of 30 people, with a purposive sampling techniques sampling. The independentvariables are parity on postpartum mother and the dependent variable is the correctfeeding position. The instrument of this research with interviews and observation sheet.Analysis of the data by using chi square test at the significant level of 0.05.Based on the results of parity On 22 Capital Ruling majority of respondents(73,3%) primiparas. Breastfeeding Correct Position On Mother Postpartum mostly 8respondents (26,7%) with a disadvantage. No Parity Relationships with the RightNursing Position On Postpartum Mothers in Hospital Muslimat Ponorogo andMuhammadiyah Ponorogo Ponorogo's Women, at significance level of 0.05 is thusobtained p = 0.000 p <α 0.05, Ha accepted that there Parity Relationships with NursingPositions properly on Postpartum Mothers in Hospita’sMuslimat Ponorogo andMuhammadiyah Ponorogo Ponorogo, with a strong degree of closeness of relationship(0.683).Based on the results of the study are expected postpartum mothers to increase theirknowledge and understanding of the importance of knowing the correct feeding position,especially for mothers primiparous.